Rastne značilnosti gorskega javorja (Acer pseudoplatanus L.) v Sloveniji - Kadunc, Aleš (Zbornik gozdarstva in lesarstva, 2003)
In the present contribution, the growth characteristics of sycamore in four site groups in Slovenia are analysed. Analyses of height and diameter growth on the basis of 191 sycamore trees from 30 different locations were carried out. Additionally, the height increments of sycamore's seedling from three locations were measured every ten days during the growing period. The results show that on maple sites the sycamore grows faster in height than the sycamoreon beech and silver fir-beech sites. Concerning the diameter growth, the sycamore on maple sites has a higher rate of growth in the early years, but is later on overtaken by sycamore from beech as well as silver fir-beech sites. The largeness of sycamore's crown influences the tree ring width. The current annual increment of height most often culminates between 12th and 14thyears of age, while diameter CAI culminates between 20th and 40th years ofage. The mean annual increment of height reaches the peak mostly between 20th and 25th years of age, while diameter MAI reaches it mostly between 30th and 50th years of age. The height increment of sycamore has a single distinct culmination in the growing period, with intensive growth of height lasting for30 to 40 days.
Keywords: Acer pseudoplatanus L.; gorski javor; rast; rastišče; Slovenija